1995
DOI: 10.1038/ki.1995.220
|View full text |Cite
|
Sign up to set email alerts
|

Zaprinast accelerates recovery from established acute renal failure in the rat

Abstract: Atrial natriuretic factor (ANF) has been demonstrated to be effective in the treatment of acute renal failure (ARF) in both rat and humans. The biological effects of ANF are presumed to be mediated by the generation of intracellular 3',5'-cyclic guanosine monophosphate (cGMP). Therefore, the current investigation examined whether zaprinast (M&B 22948), a guanosine 3',5'-cyclic monophosphate (cGMP)-specific phosphodiesterase inhibitor, would be effective in the treatment of established acute renal failure in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 34 publications
2
24
1
Order By: Relevance
“…The fall in renal cAMP level was correlated with the depression in GFR caused by the LPS challenge, suggesting the possibility that the protective effect of ␤ 2 -AR activation was exerted through the intracellular cAMP/cAMPdependent protein kinase (PKA) pathway. This would be compatible with previous reports that cAMP-PKA activation plays an important role in the protection against acute renal failure (39,40).…”
Section: Discussionsupporting
confidence: 82%
“…The fall in renal cAMP level was correlated with the depression in GFR caused by the LPS challenge, suggesting the possibility that the protective effect of ␤ 2 -AR activation was exerted through the intracellular cAMP/cAMPdependent protein kinase (PKA) pathway. This would be compatible with previous reports that cAMP-PKA activation plays an important role in the protection against acute renal failure (39,40).…”
Section: Discussionsupporting
confidence: 82%
“…Augmentation of blood flow after ischemia, either by hemodilution, treatment with atriopeptin, or removal of the contralateral nonischemic kidney, can ameliorate ischemic ARF (6). The effects of atriopeptin and nitric oxide on renal blood flow in these models are mediated by cyclic GMP, and it has been reported that inhibition of cyclic GMP phosphodiesterase with zaprinast increases renal blood flow and ameliorates ARF, even when given a full day after ischemic injury (19). It is conceivable, although not tested in the current report, that increasing intracellular guanine nucleotides affects generation of cyclic GMP, thus improving blood flow in the injured organ.…”
Section: Guanosine and Tubule Cell Survivalcontrasting
confidence: 37%
“…Guan et al (19) showed that treatment with zaprinast, a cGMP-specific phosphodiesterase inhibitor, 24 h after 60 min of bilateral renal artery clamping in the rat, accelerated renal recovery by improving regional renal blood flow. Early treatment with sildenafil ameliorated the progression of renal damage in a 5 ⁄6 nephrectomy model (32).…”
mentioning
confidence: 99%